2022
DOI: 10.3390/s22083059
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Localization of Optically Pumped Magnetometers Using Electromagnetic Coils

Abstract: In this paper, we propose a method to estimate the position, orientation, and gain of a magnetic field sensor using a set of (large) electromagnetic coils. We apply the method for calibrating an array of optically pumped magnetometers (OPMs) for magnetoencephalography (MEG). We first measure the magnetic fields of the coils at multiple known positions using a well-calibrated triaxial magnetometer, and model these discreetly sampled fields using vector spherical harmonics (VSH) functions. We then localize and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This system can also work dynamically, with constant feedback allowing drifts in field over time to be accounted for. In addition, recent work has shown that this high fidelity field control can also be exploited for calibration, as well as to identify the location and orientation of the sensors themselves [ 68 ].…”
Section: Figurementioning
confidence: 99%
“…This system can also work dynamically, with constant feedback allowing drifts in field over time to be accounted for. In addition, recent work has shown that this high fidelity field control can also be exploited for calibration, as well as to identify the location and orientation of the sensors themselves [ 68 ].…”
Section: Figurementioning
confidence: 99%
“…In practice, an SSS-guided calibration is often used to ensure optimal performance, but the operational principle of OPMs, and the potential for many different array configurations means SSS-guided approaches may be challenging to implement (as sensor calibration may vary depending on parameters, including the density of atoms in the OPM vapour cell and the background field experienced by the sensor). Methods based on the use of electromagnetic coils have been proposed in mitigation [ 24 ]. All these issues will need to be addressed to fully realise the potential of OPM-MEG.…”
Section: Discussionmentioning
confidence: 99%
“…A compromise may be the use of a limited number of different-sized rigid helmets, with holders in which OPMs can be pressed onto the scalp (Zetter et al, 2019). The depth of the OPMs within their holder could be measured manually, or sensor positions and orientations could be determined automatically, using either an optical approach (Gu et al, 2021) or utilising the field-nulling coils (Iivanainen et al, 2022). The latter approach has the advantage that any changes in the orientations of the OPM’s sensitive axes due to crosstalk from neighbouring OPMs are already taken into account.…”
Section: Discussionmentioning
confidence: 99%